On Optimality of SAFER-256 Diffusion - Knarik M. Kyuregyan (Изд-во НАН РА)
In this paper it is shown that the new block cipher SAFER-256 provides an optimal diffusion in the sense that the cipher is resistant against differential cryptanalysis attack after minimum possible number of rounds.
Keywords: Mathematics; Computer software